Peningkatan Kemampuan Kader Melalui Edukasi Pemanfaatan Bahan Alam Untuk Meningkatkan Produksi ASI Di Kelurahan Banjarsari Surakarta - Aris Prastyoningsih; Frieda Ani Noor; Maria Wisnu Kanita; Erinda Nur Pratiwi; Tresia Umarianti (Poltekkes Kemenkes Surakarta, 2021)
Background: The benefits of breastfeeding for infants include reducing infant mortality due to diarrhea and infection, reducing mortality among malnourished children, protecting against gastrointestinal infections, as well as being a source of energy and nutrition for infants aged 6 to 23 months. While the benefits for mothers who are breastfed are reducing the risk of ovarian cancer and providing breast support after milk production, as a natural prevention method in the first six months of birth, and helping to lose weight faster with pregnancy. Vegetables / natural plants that are easily available around us that can be used to increase breast milk production. Research in addition to carbohydrates, these vegetables also contain protein, minerals (phosphorus, calcium and iron, as well as a number of vitamins A, B1 and C). Methods: The method used is to present a booklet through education. The number of respondents was 20 mothers of health cadres. Results: The result of this community service activity is an increase in knowledge about the use of style materials for breastfeeding from 75% sufficient knowledge to 80% good knowledge. Conclusion: increasing knowledge and understanding of health cadres before and before providing education through natural plant booklets to increase breast milk.